2014
DOI: 10.1002/sia.5384
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigation of SnO2 catalytic nanoparticles doped with F and Sb

Abstract: Structural and morphological properties of pure and F-doped or Sb-doped particles of tin oxide were studied by X-ray diffraction and transmission electron microscopy (TEM). A typical polycrystalline diffraction pattern corresponding to the tetrahedral phase was obtained for all the particles independently of the doping. No peaks matching any antimony oxide phase were observed; thus, it is probable that Sb replaces Sn in the tin oxide lattice. Doping with antimony results in a lattice parameter increase of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…According to the SEAD patterns, the lattice parameter of d{101} α-Ti or d{102}Mg from SEAD patterns was found to be 0.233 nm or 0.214 nm. Using SAED images and XRD techniques, Magdalena et al [39] demonstrated that the lattice parameter increase of the SnO2/Sb phase was related to the geometrical distortion of the lattice due to the replacement of Sn by Sb. These results indicated the mutual dissolution between Mg and Ti.…”
Section: Microstructure and Surface Analysismentioning
confidence: 99%
“…According to the SEAD patterns, the lattice parameter of d{101} α-Ti or d{102}Mg from SEAD patterns was found to be 0.233 nm or 0.214 nm. Using SAED images and XRD techniques, Magdalena et al [39] demonstrated that the lattice parameter increase of the SnO2/Sb phase was related to the geometrical distortion of the lattice due to the replacement of Sn by Sb. These results indicated the mutual dissolution between Mg and Ti.…”
Section: Microstructure and Surface Analysismentioning
confidence: 99%
“…However, very few literature on such solution of Al-Si-N is available and is less understood. [3,[9][10][11][12] The present manuscript reports the formation of Al-Si-N hard coating by magnetron sputtering with a high optical transmittance.…”
Section: Introductionmentioning
confidence: 99%